Can local brands play the game? Institutional logics and the cultural construction of global-local dynamics of consumption - Arakelian, José Sarkis (2020)
As societal institutional logic, the effects of globalization are undisputable, being institutionalized in daily life, potentializing the construction of culture-mixing by integrating the global and local in interpenetrating processes. One way to comprehend a market system dynamic is to analyze the establishment of institutional field-level logics and the transformation of practices in the social context. As complex systems evolve through time, to understand how brands and consumers organize practices, sensemaking, and decision-making assuming diversity in consumption is the aim of this research. The existing literature on market system dynamics focuses on transformations in markets as an outcome of evolving, conflicting, or replacing logics, or even in market actors assuming one or the other excluding field-level logic. However, brands and consumers exposed to plural field-level complementary logics are still underexplored. Therefore, this research seeks to understand the market transformations resulting from this dynamic, immersed in the football context in Brazil, considering local and European global clubs’ brands. To achieve this, from a poststructuralist perspective, I developed a multimethod approach, collecting data from multiple sources and types such as overall media and marketplace data, historical magazine data, netnography on social media, participant observation, and in-depth interviews with industry experts and consumers. Two diverse but complementary institutional logics were identified, the “fun’ and the “root,” which coexist. During practices, sensemaking, and decision-making, brands and consumers do not assume one or the other in opposition, whether in the consumption decision-making process of local or global brands, but both of them, in a process of interplay.